PENGARUH PEMBERIAN EKSTRAK BAWANG MERAH (Allium cepa L.) DENGAN BERBAGAI KONSENTRASI TERHADAP PERTUMBUHAN STEK PUCUK KAYU PUTIH (Melaleuca leucadendron L.) - Mailinda Topa; Ch. Endang Purwaningsih; Leo Eladisa Ganjari (Biospektrum Jurnal Biologi, 2023)
Eucalyptus plants can be propagated vegetatively by shoot cuttings. One of the natural growth regulators that can be used to stimulate the growth of Eucalyptus shoot cuttings was shallot extract (EBM), which contains the hormone auxin which functions to stimulate plant growth. This study aims to determine the effect of EBM with various different concentrations on the growth of Eucalyptus shoot cuttings (Melaleuca leucadendron L.). Completely Randomized Design (CRD) was used in this experiment, with five treatments, with four replicates for each treatment. The concentrations used in the treatment were as follows: K- Eucalyptus shoot cuttings without EBM or NAA., K+ Positive control, Eucalyptus shoot cuttings with NAA hormone., K1 Eucalyptus shoot cuttings with 50% EBM concentration. K2 Eucalyptus shoot cuttings with EBM concentration of 60%. K3 Eucalyptus shoot cuttings with EBM concentration of 70%. Parameters observed included the number of roots, root length, root fresh weight, and number of leaves. The results of this experiment showed that the concentration of 70% EBM gave the best results on the growth of shoot cuttings of Eucalyptus (Melaleuca leucadendron L.), in number of roots (7,250 pieces), root length (13,625 cm), root fresh weight (0,560 g), and number of leaves (19.00), compared to 60% and 50% EBM, as well as the negative control.Concentration 70% EBM gave almost the same growth results as the positive control (with NAA hormone). Keywords: shallot extract (EBM), shoot cuttings, Eucalyptus